Legal Protections For Donation-Based Crowdfunding Service Providers In Indonesia - Hasibuan, Putra Halomoan (Prophetic Law Review, 2020)
This study focuses on legal protections for donation-based crowdfundingservice providers in Indonesia. It is urgent to investigate these protectionsbecause the specific legal arrangement is not clear. This research discusses the following issues: First, what is the meaning of a legal protections in the practice of donation-based crowdfunding in Indonesia? Second, what are the current legal protections, if any,for donation-based crowdfundingservice providers in Indonesia? This study carried out a qualitative normative legal research method by using a statutory approach and a conceptual approach. The object of this research is focused on those entities which haveimplemented donation-based crowdfunding. The results showed that: First, the community in Indonesia has not had a good understanding of the term ‘donation-based crowdfunding,’ still requiring socialization regarding the ways and methods of implementing it onlineeven though it has been done for a long time; andSecond, the legal protections for donation-based crowdfundingservice providers still adoptsthe regulations similar to DBC. This study recommends that the government immediately conduct socialization to the public regarding the existence of DBC in Indonesia. Furthermore, lawsand regulations specifically discussing donation-based crowdfunding should be issued immediatelyin order to address many problems that have arisen and will continue to arise as a result of these activities, especially in the field of donations.Keywords: Capital; crowdfunding; donation; investment; legal protections; partiesPerlindungan Hukum Bagi Penyedia Layanan Crowdfunding Berbasis Donasi Di IndonesiaAbstrakPenelitian ini berfokus pada perlindungan hukum bagi penyedia layanan crowdfunding berbasis donasi di Indonesia. Menyelidiki perlindungan ini adalah hal yang mendesak karena pengaturan hukum yang spesifik terkait hal ini tidak jelas. Penelitian ini membahas beberapa hal sebagai berikut: Pertama, apa yang dimaksud dengan perlindungan hukum dalam praktik crowdfunding berbasis donasi di Indonesia? Kedua, bagaimana perlindungan hukum saat ini, jika ada, bagi penyedia layanan crowdfunding berbasis donasi di Indonesia? Penelitian ini dilakukan dengan metode penelitian hukum normatif kualitatif dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Objek penelitian ini difokuskan pada entitas yang telah menerapkan crowdfunding berbasis donasi. Hasil penelitian menunjukkan bahwa: Pertama, masyarakat di Indonesia belum memiliki pemahaman yang baik tentang istilah 'crowdfunding berbasis donasi', masih membutuhkan sosialisasi mengenai cara dan metode pelaksanaannya secara online meskipun sudah dilakukan sejak lama; dan Kedua, perlindungan hukum bagi penyelenggara layanan crowdfunding berbasis donasi masih menganut aturan yang serupa dengan DBC. Kajian ini merekomendasikan agar pemerintah segera melakukan sosialisasi kepada masyarakat mengenai keberadaan DBC di Indonesia. Lebih lanjut, peraturan perundang-undangan yang secara khusus membahas crowdfunding berbasis donasi harus segera diterbitkan guna mengatasi berbagai permasalahan yang telah dan akan terus timbul akibat kegiatan tersebut, khususnya di bidang donasi.Kata kunci: Modal, Crowdfunding, Donasi, Investasi, Perlindungan Hukum, Para Pihak